Enzymatic kinetics of solvent-free esterification with bio-imprinted lipase - Matsumoto, M. (Array, 2020)
To avoid the use of compounds that burden the environment, a solvent-free enzymatic reaction was the focus of this study. Investigated were the catalytic activities and kinetics of lipases that were pretreated with carboxylic acids for the solvent-free esterification of propionic acid with isoamyl alcohol. The enhancements of the esterification yields and rates by the bio-imprinting effects of carboxylic acids were observed. We found no inhibition of isoamyl alcohol on the solvent-free enzymatic esterification, and obtained a large imprinting effect under a largely excessive amount of isoamyl alcohol to propionic acid. From the kinetic analysis, the imprinting of lipases mainly enhanced the catalytic reaction rate constant rather than the affinity between lipase and propionic acid compared with untreated lipase. The bio-imprinting treatment of lipase is found to be very effective for the yield and kinetics in solvent-free esterification.